Non-contraceptive effects of microdose folate-containing oral contraceptive in patients of child bearing age - T. M. Sokolova; K. Yu. Makarov; T. V. Kiseleva; A. V. Yakimova (Медицинский совет, 2018)
The article provides a summary of the evaluation of efficacy of folate-containing oral contraceptive (Yaz® plus) containing gestagen with antiandrogenic and antimineralocorticoid effect, which, neutralizes the symptoms of primary dysmenorrhea in addition to preventing unwanted pregnancies, and also has registered indications for the treatment of acne.